Rancang Bangun Mesin Mixer Pakan Ternak Kapasitas 100 Kilogram Per 2 Jam - Fakih Al Ghifari, Muhammad; Muhammad, Sandi; Prasetyo, Prasetyo; Daniel Saragih, Albert (Manutech : Jurnal Teknologi Manufaktur, 2024)
Complete animal feed, namely food given to livestock whose ingredients are made from processed agricultural waste. Animal feed for sheep varies, but what is good is feed made from a mixture of bran, dried kale stalks, corn buns, and dried green bean skins mixed together. Currently, there are still many breeders who use traditional methods for the process of mixing animal feed ingredients such as using human power. Based on these problems, cooperation was carried out with breeders in Sukawangi village in the framework of making a sheep feed mixer machine. The working process of the tool that is made will start from the rotation of the electric motor according to the rotation it has, then the result of this rotation of the electric motor will be accepted and reduced. The result of making a sheep feed mixer machine with a capacity of 100 kilograms which is made to have specifications (1180 x 702 x 544) mm using a wormgear motor drive system NMRV 050 0.75 HP, 3 phase, with a ratio of 1:20 from 1400 rpm motor rotation can run with a load of approximately 20 kilograms inserted with a time of 20 minutes starting from the feed ingredients that are added until the machine finishes mixing.